2015
DOI: 10.7763/ijiee.2015.v5.543
|View full text |Cite
|
Sign up to set email alerts
|

Feature Exploration for Prediction of Potential Tuna Fishing Zones

Abstract: Prediction for potential fishing zone is one of the important activities concerning for the tuna fishing exploration, conservation and management. Accurate prediction will give more efficient in fishing activities. One of the way to predict is the classification techniques. Currently, as the state of the art, most of the methods utilize the chlorophyll and SST features. However, there are still other parameters that can be utilized. In this paper, the other parameters are then observed: ocean currents and sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…As noted previously, the oceanographic parameters that are often used in studies of the determination of potential fishing zones are sea surface temperature and chlorophyll-a. According to the results of such studies, chlorophyll-a is the most influential in determining potential fishing zone [12], [13]. This proves that data on the dis-tribution of chlorophyll-a are needed to determine potential areas of fishing.…”
Section: Previous Studiesmentioning
confidence: 91%
“…As noted previously, the oceanographic parameters that are often used in studies of the determination of potential fishing zones are sea surface temperature and chlorophyll-a. According to the results of such studies, chlorophyll-a is the most influential in determining potential fishing zone [12], [13]. This proves that data on the dis-tribution of chlorophyll-a are needed to determine potential areas of fishing.…”
Section: Previous Studiesmentioning
confidence: 91%
“…But the classification results are still classified as fair classification category. In 2015 Fitrianah et al [18] conducted a potential zone study for tuna fishing using classification techniques, it was found that the last combination of features that include Chlorophyll, SST, the current Ocean and salinity gave the highest yield in classification (in Naïve Bayes reaching 69 , 03%, Decision Tree reached 82.32% and SVM achieved 68.30% accuracy) compared to "base" combination features including only Chlorophyll and SST (in Naïve Bayes reached 57.44%, Decision Tree reached 58.91% and SVM achieved 56.74% accuracy).…”
Section: Related Work Regarding To Capture Fisheriesmentioning
confidence: 99%
“…In the previous studies [5], determining the related features has been done by testing several combination of oceanographic feature sets. Then, the feature set that yields a high prediction accuracy has been chosen.…”
Section: Previous Workmentioning
confidence: 99%
“…The last combination (f 4) gives the best result, which is 82.32% using Decision Tree classification. In addition to discover the best relevant feature to the Albacore tuna PFZ [5], in this research we also wish to discover the best relevant feature to other tuna species such as Bigeye tuna.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation